ENJOY THE FANTASY OF A "V" WHILE YOU CAN. Issue 2 (2nd August 2020) - Roberts, Daniel
Abstract: "The fight against Covid-19 has seen unprecedented, but hopefully temporary, damage to the global economic system. The shape of the Covid-recession is hotly debated, and with hopes for a "V" shaped recovery, and not the double-dip "W"or a steep fall followed by a slow recovery. This article lays out the case that the damage is deep and wide, and the the recovery, even with an apparent rapid initial rebound, will be much slower than hoped. The article touches on a number of sectors and considers the damange and prospects for those sectors, and touches on the risks inherent in the fisacal policy response. "